SEBARAN DAN KARAKTERISTIK BATUAN ULTRAMAFIK SEBAGAI POTENSI NIKEL LATERIT SERTA KAITANNYA DENGAN PENYIMPANAN KARBON PADA DAERAH SOROWAKO - Sambodo, Tri Hananto Priyo; Sukiyah, Emi; Hutabarat, Johanes (Indonesian Mining Journal, 2024)
Ultramafic rocks, as the main raw material for the formation of nickel laterite in nature, are important object to study and explore for their availability since nickel is very important mineral in producing batteries for electric cars which is expected to reduce carbon emissions in the future. Along with that, the storage of carbon dioxide in ultramafic rocks is considered as one of the safest storage method because carbon dioxide reacts naturally with magnesium-rich minerals contained in these rocks. The reaction between carbon dioxide and magnesium-rich minerals such as olivine, pyroxene, and serpentine will produce magnesite (MgCO3), which is more stable in nature. Ultramafic rocks have wide distribution in southeastern arm of Sulawesi Island, especially in Sorowako and the surrounding areas. The method used in this research is an observation method on outcrops and supported by laboratory analysis. Ultramafic rocks in Sorowako area have wide distribution and have varying degrees of serpentinization. The magnesium (Mg) element contained in the research area is widely spread as well as the development of geological structure allows the potential development of ultramafic rocks as carbon storage.